New Treatment Options for Pituitary Granulomatosis With Polyangiitis - Boharoon, Hessa (J Endocr Soc, 2021)
Background: Granulomatosis with polyangiitis (GPA) rarely involves the pituitary gland and has been reported in 1% of all cases of GPA. Most frequently, it presents with pituitary mass effect and diabetes insipidus (DI). To date, there are no treatment guidelines for this rare condition. Case Presentation: Case 1: A 55 year old female with a history of ANCA-positive pulmonary GPA, previously treated with glucocorticoids and immunosuppressants, presented two years later with cranial DI and bitemporal hemianopia. MRI showed a large sellar mass with suprasellar extension. High dose glucocorticoids resulted in good clinical and radiological response. Further treatment consisted in a combination of Cyclophosphamide and Rituximab (RTX). Further doses of RTX are planned aiming for a period of B-cell depletion. Case 2: A 38 year old female, presented with polyuria, recurrent nosebleeds, headaches and a left visual field defect. Pituitary profile revealed ACTH deficiency and MRI showed a heterogenous cystic lesion with peripheral enhancement and stalk thickening. Steroid replacement led to immediate improvement in her symptoms. Cranial DI was confirmed and raised Proteinase 3 (PR3) antibody suggested GPA. A combination of prednisolone and Methotrexate led to significant improvement of MRI appearances and declining PR3 antibody levels. For remission maintenance, two cycles of RTX were given with further radiological and biochemical improvement, and, following dynamic assessment of her HPA axis, she could be fully weaned off steroids. Case 3 is a 47 year old female with a history of childhood asthma. She was found to have cavitating lung lesions. ANCA positivity confirmed GPA and she was commenced on high-dose steroids. During follow-up, she developed headache, polyuria and polydipsia. MRI pituitary showed a suprasellar lesion and pituitary biopsy revealed inflammatory hypophysitis. Cranial DI was confirmed by water deprivation testing. Previous allergic reactions to both RTX and Ofatumumab precluded anti-CD40 monoclonal antibodies and she was commenced on Azathioprine. A further recurrence of pituitary GPA necessitated escalation of the steroid dose and switch of azathioprine to mycophenolate mofetil. She remains in remission and her steroids reduced to a maintenance dose. Conclusion: GPA pituitary has been observed to occur at variable time after diagnosis often in the absence of any other systemic features. A combination of glucocorticoids and RTX has been approved for severe relapsing pulmonary GPA, however, limited data is available for pituitary GPA. In this case series, the response to high dose steroids and RTX for remission maintenance has been encouraging. Experience with ‘conventional’ immunosuppresants remains limited and therapeutic responses remain variable. Further clinical studies are required to establish effective treatment for pituitary GPA.